EFFECT OF CLIMATE CHANGE ON AGRICULTURAL SECTOR: EVIDENCE FROM NIGERIA - IME OKON UTUK; ANIEFIOK BENEDICT UDO; BONIFACE LINUS AKPAN; EDEDET BASSEY EDUNO; INIGBEHE MICHAEL OKON (International Studies Journal)
This study conducts an empirical investigation of the effects of climate change on agriculture production in Nigeria from 2000-2022.  The fully modified ordinary least squares (FMOLS) estimator was employed for estimation of the specified model. The result shows that among the climate change variables, temperature (LNTEMP) has a significant positive impact on agriculture sector while rainfall has a negative and significant effect on agricultural sector. More so, methane emissions (LNMETH) exhibited an inverse relationship with agriculture sector. Carbon dioxide emission (LNCO2) shows a positive but insignificant relationship with agriculture sector. In that regard, the Federal government needs to invest in agricultural science research so that scientists can produce crops that are resistant to the harsh climatic conditions. At the same time, climate-smart agricultural innovations to conserve water such as solar-powered drip irrigation and rainwater harvesting should be concentrated on to help farmers cope with droughts. Also, farmers can cut emissions by improving fertilizer use.